Studi Penciptaan Karya Seni Grafis Dengan Teknik Hot Print Di Atas Kaca - Zarkasi, Much. Sofwan (Brikolase : Jurnal Kajian Teori, Praktik dan Wacana Seni Budaya Rupa, 2009)
The development of discourse as well as the work process in the fine art realm relates to the contem-porary art spirit bringing pluralism, generates the tendency of art limit loss and daily needs, the fall of barriers between the high and popular cultures, opens the oppor-tunities of exploring form, technique and medium in creating the art work. The art institution and artist are required to attend and to participate actively in the dynamics of art development. A study on art work creation occurring from the observation, trial and creative experimentation is one proper answer for the demand of art development. This study begins from the observation of technique deve-lopment in the fine art work on the glass medium that still open the opportunity to explore the working technique, and it is inspired by the graphical art development beginning to expand to the computer tech-nology. The author wants to produce a fine art work with glass medium that is different from conventional glass pain-ting art and the technique employed was the printing technique in the graphical technique using thermal energy or called Hot Print. The hot print technique it self is a printing technique that utilize thermal energy in this case using the heat conductor plate connected to the electricity during the transfer of image to the drawing medium consti-tuting cloth, ceramic or glass. Mean-while, the experimentation the author stimulates is the picture visualization processing on the glass that later seems to be three dimensions, with the piled layer or glass system. In addition, the author also tries to present the problem, that is, questioning the communal identity of Javanese society amid the global culture, through Panakawan charac-ter, that is Bagong. Keyword: Wayang, Graphic art, Hot Print technique.